Service Quality Can Determine Patient’s Loyalty in Internal Disease Inpatient Room at Dr. Sismadi Cileungsi Bogor Hospital - Nurhadi Nurhadi (Program Studi Magister Manajemen Rumah Sakit, Jenjang Pasca Sarjana (S2), Pasca Sarjana Universitas Muhammadiyah Yogyakarta, 2021)
Improving the quality of services provided by hospitals to patients will be able to create a sense of patient satisfaction, so that the creation of a sense of patient satisfaction will lead to a loyal attitude of patients towards hospital services. This study aims to analyze the effect of service quality and patient satisfaction on patient loyalty in the inpatient department of Dr. Sismadi. The design of this study was the design of causality with 170 inpatients in the internal medicine department at Dr. Hospital. Sismadi. Samples were taken by using purposive sampling technique. Service quality and patient satisfaction variables are independent variables and patient loyalty is the dependent variable. The research instrument was a questionnaire and was measured on an interval scale. Data were analyzed using SEM-LISREL. The results showed that the variable service quality had a positive effect on patient loyalty. Service quality has a positive effect on patient satisfaction meaning to increase patient loyalty, the level of satisfaction is improved through improving service quality, and patient satisfaction has a positive effect on patient loyalty. The dominant variable is service quality